Plasma proteome in multiple sclerosis disease progression. Issue 9 (31st July 2019) - Malekzadeh, Arjan; Leurs, Cyra; van Wieringen, Wessel; Steenwijk, Martijn D.; Schoonheim, Menno M.; Amann, Michael; Naegelin, Yvonne; Kuhle, Jens; Killestein, Joep; Teunissen, Charlotte E.
Abstract: Background: The pathophysiology of multiple sclerosis disease progression remains undetermined. The aim of this study was to identify differences in plasma proteome during different stages of MS disease progression. Methods: We used a multiplex aptamer proteomics platform (Somalogic) for sensitive detection of 1129 proteins in plasma. MS patients were selected and categorized based on baseline and a 4‐year follow‐up EDSS (delta EDSS) scores; relapse‐onset (RO) slow progression ( n  = 31), RO with rapid progression ( n  = 29), primary progressive ( n  = 30), and healthy controls ( n  = 20). The relation of baseline plasma protein levels with delta EDSS and different MRI progression parameters were assessed using linear regression models. Results: Regression analyses of plasma proteins with delta EDSS showed six significant associations. Strong associations were found for the proteins LGLAS8 ( P  = 7.64 × 10 −5, q  = 0.06), CCL3 ( P  = 0.0001, q  = 0.06), and RGMA ( P  = 0.0005, q  = 0.09). In addition, associations of plasma proteins were found with percentage brain volume for C3 ( P  = 2, 08 × 10 −9, q  = 1, 70 × 10 −6 ), FGF9 ( P  = 3, 42 × 10 −9, q  = 1, 70 × 10 −6 ), and EHMT2 ( P  = 0.0007, q  = 0.01). Most of the significant markers were associated with cell‐cell and cell‐extracellular matrix adhesion, immune system communication, immune system activation, and complement pathways. Conclusions: Our results revealed eight novel biomarkers related to clinical and radiological progression in MS. These results indicate that changes in immune system, complement pathway and ECM remodeling proteins contribute to MS progression and may therefore be further explored for use in prognosis of MS.